Muslim televangelists voices of islam's future (Films Media Group, 2009)
These superstar preachers bring the word of Allah straight to TV, computer, or mobile phone. They're changing the image of extremism that Islam struggles to shrug off. This documentary gets up close and personal with evangelist preachers like Amr Khaled, who are hailed as the future of Islam. "Islamic religious discourse has stagnated in the last 200 years," Amr Khaled says to a captivated crowd. "It has failed to respond to current issues in society." He speaks for an hour, and leaves his audience of mostly young and female Muslims in tears. With Time magazine voting Amr Khaled the 13th most influential person in the world, he charts a phenomenon that is finally bringing Islam up to speed with the modern world.